Dukungan Keluarga dan Work Life Balance Saat Pandemi COVID-19 - Tigowati Tigowati (FORIKES, 2022)
The Coronavirus disease (COVID-19) pandemic hit Indonesia in early 2020 and affected various aspects of life, including the work-life balance of workers. Work-life balance can be achieved if a person is able to balance roles and responsibilities at work and personal life. On the other hand, family support is also needed to support work-life balance during the COVID-19 pandemic. This study aimed to determine the effect of family support on work-life balance. This study employed quantitative research with a cross-sectional research design. The population was 59 workers PT Industri Kereta Api (Persero). The data was obtained using a valid and reliable questionnaire. The variables studied were family support and work-life balance. In analyzing the data, the researcher used descriptive analysis and linear regression analysis. The majority of workers in this study received moderate family support, namely 35 workers or 59.3%. Most of the workers had a work-life balance in the medium category, namely 66.1%. Moreover, no one worker had a work-life balance in the high category. The results showed that family support had a significant positive effect on work-life balance (Beta=0,566). Therefore, it can be concluded that the higher the family support, the higher work-life balance of workers. The recommendation of this study is to optimize the implementation of policies related to family support and provide counseling facilities. Keywords: COVID-19 pandemic; family support; work-life balanceABSTRAK Pandemi Coronavirus disease (COVID-19) melanda Indonesia pada awal 2020 berpengaruh pada berbagai aspek kehidupan. Tidak terkecuali mempengaruhi work life balance pekerja. Work life balance dapat tercapai apabila seseorang mampu menyeimbangkan peran dan tanggung jawab pada pekerjaan dan kehidupan pribadi. Disisi lain dukungan dari keluarga juga diperlukan untuk mendukung work life balance saat pandemi COVID-19. Tujuan penelitian ini yaitu menganalisis pengaruh dukungan keluarga terhadap work life balance. Penelitian ini adalah penelitian kuantitatif dengan rancang bangun cross sectional. Total populasi dengan jumlah 59 pekerja PT Industri Kereta Api (Persero). Pengumpulan data menggunakan kuesioner yang valid dan reliabel. Variabel yang diteliti adalah dukungan keluarga dan work life balance. Teknik analisis data menggunakan analisis deskriptif dan analisis regresi linier. Mayoritas pekerja pada penelitian ini mendapatkan dukungan keluarga sedang yaitu sebanyak 35 pekerja atau sebesar 59,3%. Sebagian besar pekerja memiliki work life balance dalam kategori sedang yaitu sebesar 66,1%. Pekerja tidak ada yang memiliki work life balance dalam kategori tinggi. Hasil penelitian menunjukkan terdapat pengaruh positif dukungan keluarga terhadap work life balance (Beta=0,566). Semakin tinggi dukungan keluarga yang diperoleh pekerja maka cenderung akan meningkatkan work life balance. Saran yang diberikan untuk perusahaan adalah mengoptimalkan kebijakan terkait dukungan keluarga dan menyediakan konseling pada klinik perusahaan.Kata kunci: pandemi COVID-19; dukungan keluarga; work life balance